2017
DOI: 10.1177/0003319717739720
|View full text |Cite
|
Sign up to set email alerts
|

Raised Fibrinogen Levels and Outcome in Outpatients With Peripheral Artery Disease

Abstract: The influence of raised fibrinogen levels on outcome in stable outpatients with peripheral arterial disease (PAD) has not been consistently investigated. We used data from the Factores de Riesgo y ENfermedad Arterial (FRENA) registry to compare ischemic events, major bleeding, and mortality in stable outpatients with PAD, according to their baseline plasma fibrinogen levels. Of 1363 outpatients with PAD recruited in FRENA, 558 (41%) had fibrinogen levels >450 mg/100 mL. Over 18 months, 43 patients presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…On the one hand, inflammatory factors such as CRP can directly inhibit EPC survival, differentiation, and angiogenic potency [28]. Fibrinogen also plays a leading role in thrombosis, and elevated fibrinogen can increase the cumulative rates of ischemic events in the course of PAD [29, 30]. Our results revealed that both fibrinogen > 4 g/L and CRP > 3 mg/L can be predictors that are independent of the other factors.…”
Section: Discussionmentioning
confidence: 87%
“…On the one hand, inflammatory factors such as CRP can directly inhibit EPC survival, differentiation, and angiogenic potency [28]. Fibrinogen also plays a leading role in thrombosis, and elevated fibrinogen can increase the cumulative rates of ischemic events in the course of PAD [29, 30]. Our results revealed that both fibrinogen > 4 g/L and CRP > 3 mg/L can be predictors that are independent of the other factors.…”
Section: Discussionmentioning
confidence: 87%
“…Altes et al explored the outcome of patients with stable PAD and raised fibrinogen levels in the outpatient setting. [2] Their findings showed that during 18 months of follow up these patients with raised fibrinogen had a two-fold increase in the rate of ischemic stroke, limb amputation and death. Establishing fibrinogen as an independent risk factor for prognosis of patients with PAD has been a topic of interest.…”
Section: Discussionmentioning
confidence: 97%
“…Fibrinogen has a wellknown impact on clot strength [22]. Fibrin-clot property can affect the risk of PAD, including the premature disease, and CV outcomes [14,[23][24][25]. In addition, fibrinolytic activity affects cardiovascular outcomes in high-risk patients, as best shown for the PLATO (PLATelet inhibition and patient Outcomes) trial [26].…”
Section: Hypercoagulability/fibrinolysis and Padmentioning
confidence: 99%